Determinants of post COVID-19 clinic attendance among SARS-CoV-2-infected individuals in Stockholm, Sweden: a population-based cohort study - Anders Ternhag; Pontus Nauclér; Pontus Hedberg; John Karlsson Valik; Peder af Geijerstam; Christer Almgren-Lidman (BMJ Open)
Objectives Investigate determinants of post-COVID-19 condition (PCC) clinic attendance among participants not hospitalised versus hospitalised during the SARS-CoV-2 infection.Design Retrospective cohort study.Setting Six population-based registers with high coverage to cover all adults residing in Stockholm County, Sweden.Participants Adults residing in Stockholm County on 31 January 2020, with a SARS-CoV-2 infection through 30 November 2022, who did not die or move out of Stockholm County within 90 days.Primary outcome measures PCC clinic attendance from 90 days after the SARS-CoV-2 test until date of death, date of moving out, or 30 November 30,2023.Results Of non-hospitalised and hospitalised participants, 737 of 464 674 (0.2%) and 433 of 23 374 (1.9%), respectively, attended a PCC clinic. A total of 75 878 (16.3%) of non-hospitalised participants and 6190 (26.5%) of hospitalised participants presented with new-onset symptoms that could indicate PCC in primary care. The strongest determinants of attendance among non-hospitalised participants were mental health disorder (adjusted risk ratio (aRR) 2.57, 95% CI 2.21 to 2.98), asthma (2.39, 1.97–2.92) and >4 PCC symptoms in 2019 (2.27, 1.60–3.24), and among hospitalised participants were >31 sick days in 2019 (1.94, 1.47–2.56), 1–30 sick days in 2019 (1.56, 1.06–2.29) and obesity (1.51, 1.19–1.93). The most common clinical presentation was fatigue (n=526, 71.4%) among non-hospitalised and dyspnoea (n=148, 34.2%) among hospitalised participants.Conclusions PCC clinic attendance characteristics differed between non-hospitalised and hospitalised participants. Distinguishing PCC from conditions with overlapping symptoms and determining the appropriate level of care may be challenging, with risk of resource displacement effects and inappropriate care.